Supernatural and philosophy : metaphysics and monsters for idjits - Foresman, Galen A. (Chichester, West Sussex, United Kingdom : Wiley-Blackwell, 2013)
No doubt the years hunting monsters and saving the universe have had their toll on the Winchesters, but their toughest and most gruesome battles are contained in this book. Think Lucifer was diabolically clever? Think again. No son is more wayward than the one who squanders his intellect and academic career pursuing questions as poignant as "Half-awesome? That's full-on good, right?" Gathered here for the first time since the formation of Purgatory, a collection of research so arcane and horrific that it would make even the late, great Bobby Singer blush. Supernatural and Philoso.
pt. 1. Of monsters and morals -- pt. 2. Life, liberty, and the apocalypse -- pt. 3. Evil by design -- pt. 4. It's supernatural.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed September 20, 2013).
Keywords: Supernatural (Television program : 2005- ); Supernatural (Television program : 2005- ); PERFORMING ARTS -- Reference; Electronic books